2021
DOI: 10.1101/2021.05.04.21256514
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early pre-exposure prophylaxis (PrEP) discontinuation among pregnant and postpartum women: Implications for maternal PrEP roll out in South Africa

Abstract: IntroductionOral pre-exposure prophylaxis (PrEP) is a safe and effective prevention strategy to reduce women’s risk of HIV in pregnancy and postpartum. Effective PrEP requires daily PrEP adherence, but little is known about maternal PrEP continuation and risk factors that influence optimal PrEP use.MethodsThe PrEP in pregnancy and postpartum (PrEP-PP) study is an ongoing cohort study that enrolled consenting pregnant, HIV-uninfected women at first antenatal care (ANC) visit, followed through 12-months postpart… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Little is known about pharmacologic adherence measures during pregnancy and postpartum and about the factors related to optimal adherence during periods of sexual activity [8]. Prior studies demonstrated that pregnant and breastfeeding women (PBFW) using PrEP may struggle with daily use and continuation because of various personal, interpersonal or healthcare access barriers [9–11].…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about pharmacologic adherence measures during pregnancy and postpartum and about the factors related to optimal adherence during periods of sexual activity [8]. Prior studies demonstrated that pregnant and breastfeeding women (PBFW) using PrEP may struggle with daily use and continuation because of various personal, interpersonal or healthcare access barriers [9–11].…”
Section: Introductionmentioning
confidence: 99%
“…For example, persons whose PrEP indication predominantly stems from living in a community with high HIV incidence rates would be likely to have sustained risk [10]. Although some people likely stop PrEP because of a change in indication and in consultation with their providers, many stop because of (accurate or inaccurate) change in risk perception [37–40], adverse effects that might be manageable [37,38,40–42,43 ▪ ], pressure from partners [41], the end of pregnancy [41], or problems with payment for PrEP and related medical services or problems with access to PrEP care [37,39,40,43 ▪ ,44].…”
Section: Addressing the Preexposure Prophylaxis Cliffmentioning
confidence: 99%